Analisis Nilai Tegangan Terhadap Variasi Cekungan pada Pelat Baja Menggunakan Finite Element Method - Yoganata, Yehezkiel Septian; Purwitasari, Kartika; Cahyani, Kharisma Nur; Fajarwati, Anisah Nur (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The need for high-rise buildings is increasing as land is limited. Buildings made of steel materials are very good at resisting lateral forces. It is very necessary to analyze the mechanical properties of steel to know that the material can effectively resist the load. Modeling of steel plate material with width of 10 mm, thickness of 1 mm and height of 20 mm. Modeling was done using the Abaqus program with four variations of shell radius 0.01, 0.05, 0.1, and 0.2. Von Mises (tensile) stress results were obtained at the horizontal position of the basin at points A (radius point), B (center), and C (edge). For all modeling variations, the highest stress is at point A and then the stress value decreases to point B and then to point C. The most significant difference in value at each point is obtained for a radius variation of 0.2 with the value of each point A = 2.24059 MPa, B = 1.02566, and C = 0.64195. The steel plate variation with a radius of 0.2 has the largest deformation compared to the other variations. It can be concluded that the steel plate with a radius of 0.2 is more likely to be damaged. In the maximum principal stress value, the 0.2 radius variation also has the largest value compared to other variations.